2018
DOI: 10.1371/journal.pone.0190169
|View full text |Cite
|
Sign up to set email alerts
|

Ancient mitogenomes of Phoenicians from Sardinia and Lebanon: A story of settlement, integration, and female mobility

Abstract: The Phoenicians emerged in the Northern Levant around 1800 BCE and by the 9th century BCE had spread their culture across the Mediterranean Basin, establishing trading posts, and settlements in various European Mediterranean and North African locations. Despite their widespread influence, what is known of the Phoenicians comes from what was written about them by the Greeks and Egyptians. In this study, we investigate the extent of Phoenician integration with the Sardinian communities they settled. We present 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 51 publications
4
10
0
Order By: Relevance
“…Notably, they show strong genetic relationships to ancient North-African and eastern Mediterranean sources. These results mirror other emerging ancient DNA studies 37,58 , and are not unexpected given that the Punic center of Carthage on the North-African coast itself has roots in the eastern Mediterranean. Interestingly, the Monte Sirai individuals, predating the Villamar individuals by several centuries, show less North-African ancestry.…”
Section: S S Se Se S S a A A A A A A A E Se E E E E E E E E E Se S A Asupporting
confidence: 85%
See 1 more Smart Citation
“…Notably, they show strong genetic relationships to ancient North-African and eastern Mediterranean sources. These results mirror other emerging ancient DNA studies 37,58 , and are not unexpected given that the Punic center of Carthage on the North-African coast itself has roots in the eastern Mediterranean. Interestingly, the Monte Sirai individuals, predating the Villamar individuals by several centuries, show less North-African ancestry.…”
Section: S S Se Se S S a A A A A A A A E Se E E E E E E E E E Se S A Asupporting
confidence: 85%
“…Olivieri et al 36 analyzed 21 ancient mitogenomes from Sardinia and estimated the coalescent times of Sardinianspecific mtDNA haplogroups, finding support for most of them originating in the Neolithic or later, but with a few coalescing earlier. Finally, Matisoo-Smith et al 37 analyzed mitogenomes in a Phoenician settlement on Sardinia and inferred continuity and exchange between the Phoenician population and broader Sardinia. One additional study recovered β-thalessemia variants in three aDNA samples and found one carrier of the cod39 mutation in a necropolis used in the Punic and Roman periods 38 .…”
mentioning
confidence: 99%
“…Historically, both of these seem plausible. Sardinia hosted major Phoenician colonies in the first millennium BCE, principally along the south and west coasts of the island, and previous studies based on uni-parentally inherited markers have found evidence for Phoenician contact and gene flow (Z alloua et al , 2008; M atisoo -S mith et al , 2018). Sardinia was also an important Roman province and then was later under occupation by the Vandals and the Byzantine Empire.…”
Section: Discussionmentioning
confidence: 97%
“…O livieri et al (2017), in a companion project to the work described here, analyzed 21 ancient mitogenomes from Sardina as well as 3,491 mitogenomes from contemporary Sardinians and estimated the coalescent times of Sardinian-specific mtDNA haplogroups finding support for most of them originating in the Neolithic or later, but with a few coalescing earlier. Finally, M atisoo -S mith et al (2018) analyzed mitogenomes in a Phoenician colony on Sardinia and found evidence of continuity and exchange between the colony and broader Sardinia. Despite the initial insights these studies reveal, none of them analyze genome-wide autosomal data, which has proven to be of great use for studies of population history (P ickrell and R eich , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As U5 haplogroup was not uncommon in Neolithic European samples, and its presence in North Africa might be due to prehistoric migrations, an alterative explanation would be that haplogroup U5 was incorporated into the Berber mtDNA pool before the Carthaginians were established in Tunisia. Recently, Matisoo-Smith et al [99] published thirteen complete mitogenomes from Punic-Phoenician samples from Lebanon and Sardinia. The only haplogroups in common with the indigenous population of the Canary Islands are H3 and H1e1a, although, in this case, the Phoenician H1e1a sample is classified within the sub-lineage H1e1a10.…”
Section: Discussionmentioning
confidence: 99%